Coastal Talitridae (Amphipoda: Talitroidea) from north-western Australia to Darwin with a revision of the genus Cochinorchestia Lowry & Peart, 2010 - Lowry, J.k.; Springthorpe, R.t. (Zootaxa, 2015)
Three species of coastal talitrids are reported from north-western Western Australia: Australorchestia tantabiddyensis sp. nov., from Tantabiddy Rockholes Cave, Cape Range National Park; Talorchestia dampieri sp. nov. from Roebuck Bay, Broome and Cygnet Bay, King Sound; and Tropicorchestia derbyensis gen. et sp. nov. from Derby, King Sound. Five species are reported from west of Darwin, Northern Territory: Cochinorchestia lindsayae sp. nov.; Cochinorchestia metcalfeae sp. nov.; Floresorchestia limicola (Haswell, 1880); Microrchestia ntensis sp. nov.; and Tropicorchestia glasbyi sp. nov. The genus Cochinorchestia Lowry & Peart, 2010 is revised: Orchestia notabilis of Griffiths, 1973 is assigned to the new species Cochinorchestia morrumbene sp. nov. from Mozambique; Orchestia sp. of Ledoyer, 1979 is assigned to the new species Cochinorchestia poka sp. nov. from Ambon, eastern Indonesia; and Orchestia notabilis of Ledoyer 1986 is assigned to the new species Cochinorchestia tulear sp. nov. from south-western Madagascar. Microrchestia sp. of Bussarawich 1985 appears to be an undescribed species of Cochinorchestia from Thailand. We introduce the term virgula dentata to describe the highly modified tip of antenna 2 in talitrid amphipods and propose a theory for the age and current distribution of the family.